A new approach to breast cancer terminology based on the anatomic site of tumour origin: The importance of radiologic imaging biomarkers. Issue 149 (April 2022) - Tabár, László; Dean, Peter B.; Lee Tucker, F.; Yen, Amy Ming-Fang; Chen, Sam Li-Sheng; Jen, Grace Hsiao Hsuan; Wang, Jackson Wei-Chun; Smith, Robert A.; Duffy, Stephen W.; Chen, Tony Hsiu-Hsi
Highlights: The anatomic site of breast cancer origin determines patient outcome. The mammographic presentation of breast cancer indicates the site of origin. The unique large format, 3-D histology images support the mammographic biomarkers. Long-term patient outcome confirms the validity of mammographic imaging biomarkers. Classification by site of origin helps overcome inconsistencies in histopathology terminology. Abstract: Purpose: To use mammographic tumour features (imaging biomarkers) to classify breast cancer according to its apparent anatomic site of origin in the new era where tumours are found at their nonpalpable, earliest detectable phase. Method: Large format, subgross, three-dimensional histopathologic images of breast cancer subtypes and their corresponding imaging biomarkers were correlated with large format thin section histopathology and long-term patient outcome. Results: This systematic correlation indicates that breast cancers arise from three separate fibroglandular tissue components: the terminal ductal lobular units (TDLUs), the major lactiferous ducts, and in the stem cells of the mesenchyme. The resulting three cancer subgroups have distinctly different clinical, histopathological and mammographic presentations and different long-term outcomes. The relative frequency of these three breast cancer subgroups is approximately 75%, 20% and 5%, respectively. Classification of breast cancers according to their anatomic site of origin, as demonstrated with breast imaging and confirmed by subgross histopathology, correlates closely with the long-term patient outcome. Conclusions: Classification of breast cancers according to their site of origin helps overcome the inconsistencies in the current histopathologic terminology with its ductal-lobular dichotomy. The ability of the imaging biomarkers to determine the site of tumour origin and serve as a prognostic indicator emphasizes the increasingly crucial role of breast imaging in the management of breast cancer. Basing breast cancer management upon anatomically relevant terminology challenges the conventional mindset. Our proposals are based on research results from an unprecedented number of prospectively collected nonpalpable breast cancers diagnosed at their earliest detectable phases and followed up for several decades. This article is a general introduction to a series of forthcoming articles describing in detail the breast malignancies originating from the three sites of origin.